Lithological influence on Li isotope fractionation during silicate weathering - Chris T.L. Cheung; Brian Beaty; Kohen W. Bauer; Cody L. Colleps; Dan Asael; Sean A. Crowe; Noah J. Planavsky; Paul S. Savage; N. Ryan McKenzie (Geochimica et Cosmochimica Acta, 2026)

Petrologic and geochemical evolution of carbonates of South Bruce region, Southwest Ontario: Dolomite petrogenesis and fluid flow evolution - Ihsan S. Al-Aasm; Richard Crowe; Marco Tortola (Marine and Petroleum Geology, 2025)

Environmental exposure assessment in the international prospective study of Chronic Kidney Disease of UnceRtain Etiology (CKDu) in Agricultural Communities (CURE) research consortium: Design and protocol development - Marvin González-Quiroz; Anna Aceituno; Shuchi Anand; Alexander van Geen; Lawrence S. Engel; Emmanuel Jarquin; Clemens Ruepert; Nicole Villegas-González; Mariela Arias-Hidalgo; Nora Franceschini; Daylin Anchía-Pastrán; Karla Solano-Diaz; et al. (Science of The Total Environment, 2025)

Liver structure and function in yellowtail kingfish, Seriola lalandi, in response to alternative oils in feed - Benjamin H. Crowe; James O. Harris; Todd J. McWhorter; Matthew S. Bansemer; David A.J. Stone (Aquaculture, 2025)

Clinical Implication of Anthropometric Indices Compared to the Gold Standard Air Displacement Plethysmography (BODPOD) for Body Composition Assessment in a Racially Diverse Sample - S. Sarihi; D. Mensah; M. Qiao; J. DiNatale; A. Ellis; K. Crowe-White (Journal of the Academy of Nutrition and Dietetics, 2024)

Determining Best Practice for Tetrapolar Electrode Placement for Whole-body Bioelectrical Impedance Analysis (BIA) - D. Godson; S. Sarihi; J. DiNatale; A. Ellis; K. Crowe-White (Journal of the Academy of Nutrition and Dietetics, 2024)

Salinity, mineralogy, porosity, and hydrodynamics as drivers of carbon burial in urban mangroves from a megacity - Laetitia Allais; Benoit Thibodeau; Nicole S. Khan; Sean A. Crowe; Stefano Cannicci; Christelle Not (Science of The Total Environment, 2024)

Shape and Size Variation in Elapid Snake Fangs and the Effects of Phylogeny and Diet - Alessandro Palci; Michael S. Y. Lee; Jenna M. Crowe-Riddell; Emma Sherratt (Evolutionary Biology, 2023)
Recent studies have found correlations between the shape of snake teeth/fangs and diet. These studies were done at a very broad phylogenetic scale, making it desirable to test if correlations are still detectable at a narrower evolutionary scale, specifically within the family Elapidae. To this end, we studied fang shape in a dense selection of elapids representing most genera worldwide (74%). We used three-dimensional geometric morphometrics to analyse fang diversity and evaluate possible correlations between fang shape, fang size, and diet. We detected weak phylogenetic signal for both shape and absolute fang size, and found that evolutionary allometry contributes a small proportion of the among-species variation. The distribution of elapid fangs in morphospace was found to be surprisingly conservative, with only a few outliers. The only three dietary categories that were found to have a significant effect on fang shape are mammals, lizards, and reptile eggs, with mammals having a significant effect also on absolute but not relative fang size. Our results show that there are disparate patterns in fang-diet relationships at different evolutionary scales. Across all venomous snakes, previous work found that fangs are strongly influenced by diet, but within elapids our study shows these same associations are weaker and often non-significant. This could result from limitations in these types of studies, or could reflect the fact that elapids are a relatively young clade, where recent extensive divergences in diet have yet to be mirrored in fang shape, suggesting a lag between changes in ecology and dental morphology.

A global assessment of forest integrity within Key Biodiversity Areas - Olivia Crowe; Alison E. Beresford; Graeme M. Buchanan; Hedley S. Grantham; Ashley T. Simkins; James E.M. Watson; Stuart H.M. Butchart (Biological Conservation, 2023)

Population structure and reproductive states of the dogwhelk Nucella lapillus differ between artificial structures and natural rocky shores - Bryan Thompson; Paul R. Brooks; Veronica Farrugia Drakard; Fiona Kubin; Hannah S. Earp; Ignacio Alvarez-Cienfuegos; Pippa J. Moore; Tasman P. Crowe (Marine Environmental Research, 2023)

Targeting de novo loss-of-function variants in constrained disease genes improves diagnostic rates in the 100,000 Genomes Project - Eleanor G. Seaby; N. Simon Thomas; Amy Webb; Helen Brittain; Ana Lisa Taylor Tavares; J. C. Ambrose; P Arumugam; R Bevers; M Bleda; F Boardman-Pretty; C. R. Boustred; H Brittain; et al. (Human Genetics, 2023)
Background Genome sequencing was first offered clinically in the UK through the 100,000 Genomes Project (100KGP). Analysis was restricted to predefined gene panels associated with the patient’s phenotype. However, panels rely on clearly characterised phenotypes and risk missing diagnoses outside of the panel(s) applied. We propose a complementary method to rapidly identify pathogenic variants, including those missed by 100KGP methods. Methods The Loss-of-function Observed/Expected Upper-bound Fraction (LOEUF) score quantifies gene constraint, with low scores correlated with haploinsufficiency. We applied DeNovoLOEUF, a filtering strategy to sequencing data from 13,949 rare disease trios in the 100KGP, by filtering for rare, de novo, loss-of-function variants in disease genes with a LOEUF score < 0.2. We compared our findings with the corresponding patient’s diagnostic reports. Results 324/332 (98%) of the variants identified using DeNovoLOEUF were diagnostic or partially diagnostic (whereby the variant was responsible for some of the phenotype). We identified 39 diagnoses that were “missed” by 100KGP standard analyses, which are now being returned to patients. Conclusion We have demonstrated a highly specific and rapid method with a 98% positive predictive value that has good concordance with standard analysis, low false-positive rate, and can identify additional diagnoses. Globally, as more patients are being offered genome sequencing, we anticipate that DeNovoLOEUF will rapidly identify new diagnoses and facilitate iterative analyses when new disease genes are discovered.

The population structure, sex ratio and reproductive potential of limpets (Patella spp.) on natural shores and artificial structures in the Irish Sea - Hannah S. Earp; Ruby George; Paul R. Brooks; Veronica Farrugia Drakard; Bryan J. Thompson; Benjamin Fisher; Róisín Hayden; Tasman P. Crowe; Pippa J. Moore (Marine Environmental Research, 2023)

Assessing discards in an illegal small-scale fishery using fisher-led reporting - T. Mendo; J. Mendo; J. M. Ransijn; I. Gomez; P. Gil-Kodaka; J. Fernández; R. Delgado; A. Travezaño; R. Arroyo; K. Loza; P. McCann; S. Crowe; et al. (Reviews in Fish Biology and Fisheries, 2022)
About a third of all marine fish in the world are caught in Small-Scale Fisheries (SSF). SSF are increasingly recognised as essential for food security and livelihoods for vulnerable and economically fragile communities globally. Although individual SSF vessels are usually perceived as having little impact on the ecosystem, the cumulative impact of gear type and number of vessels may be substantial. Bottom trawling is a common fishing method that can greatly influence the marine ecosystem by damaging the seafloor and generating high levels of discards. However, appropriate sampling coverage using on-board observer programmes to collect these data from SSF are rare, as they are expensive and pose logistical constraints. A mobile App was used to assess whether self-reporting by fishers could provide reliable fine-scale information on fishing effort and discards over time in an illegal shrimp trawling fishery in northern Peru. Maps depicting the spatial distribution of trawling effort and the proportion of discards from observers and fishers were compared using the Similarity in Means (SIM) Index, which ranges from 0 when spatial patterns differ completely to 1 when spatial patterns are very similar. High levels of agreement between spatio-temporal patterns of effort (SIM Index = 0.81) and discards (0.96) were found between fisher and observer maps. Moreover, far greater spatial coverage was accomplished by fishers, suggesting that self-reporting via an App represents a useful approach to collect reliable fisheries data as an initial step for effective monitoring and management of these fisheries.

Phanerozoic history of the Pilbara region: implications for iron mineralisation - C. S. Perring; J. M. A. Hronsky; M. Crowe (Australian Journal of Earth Sciences, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Determining tolerance levels for quality assurance of 3D printed bolus for modulated arc radiotherapy of the nose - T. Kairn; S. Talkhani; P. H. Charles; B. Chua; C. Y. Lin; A. G. Livingstone; S. K. Maxwell; T. Poroa; E. Simpson-Page; E. Spelleken; M. Vo; S. B. Crowe (Physical and Engineering Sciences in Medicine, 2021)

Clinical implementation of a Monte Carlo based independent TPS dose checking system - A. G. Livingstone; S. B. Crowe; S. Sylvander; T. Kairn (Physical and Engineering Sciences in Medicine, 2020)

Quasi-simultaneous 3D printing of muscle-, lung- and bone-equivalent media: a proof-of-concept study - T. Kairn; M. Zahrani; N. Cassim; A. G. Livingstone; P. H. Charles; S. B. Crowe (Physical and Engineering Sciences in Medicine, 2020)

Assessing the fit of 3D printed bolus from CT, optical scanner and photogrammetry methods - S. K. Maxwell; P. H. Charles; N. Cassim; T. Kairn; S. B. Crowe (Physical and Engineering Sciences in Medicine, 2020)

Rates and Pathways of N2 Production in a Persistently Anoxic Fjord: Saanich Inlet, British Columbia - Céline C. Michiels; Julia A. Huggins; Karina E. Giesbrecht; Jenifer S. Spence; Rachel L. Simister; Diana E. Varela; Steven J. Hallam; Sean A. Crowe (Frontiers in Marine Science, 2019)

Future Directions in the Research and Management of Marine Snakes - Vinay Udyawer; Peter Barnes; Xavier Bonnet; François Brischoux; Jenna M. Crowe-Riddell; Blanche D’Anastasi; Bryan G. Fry; Amber Gillett; Claire Goiran; Michael L. Guinea; Harold Heatwole; Michelle R. Heupel; et al. (Frontiers in Marine Science, 2018)

Characterization of large basking shark Cetorhinus maximus aggregations in the western North Atlantic Ocean - L. M. Crowe; O. O'Brien; T. H. Curtis; S. M. Leiter; R. D. Kenney; P. Duley; S. D. Kraus (Journal of Fish Biology, 2018)
Cetorhinus maximus aggregations recorded during extensive aerial survey efforts off the north‐eastern United States between 1980 and 2013 included aggregations centring on sightings with group sizes of at least 30 individuals. These aggregations occurred in summer and autumn months and included aggregation sizes of up to 1398 individuals, the largest aggregation ever reported for this species. The aggregations were associated with sea surface temperatures of 13–24° C and chlorophyll‐a concentrations of 0·4–2·6 mg m −3 and during one aggregation, a high abundance of zooplankton prey was present. Photogrammetric tools allowed for the estimation of total body lengths ranging between 4 and 8 m. Characterization of these events provides new insight into the potential biological function of large aggregations in this species.

Metabolic impact of 100% fruit juice consumption on antioxidant/oxidant status and lipid profiles of adults: An Evidence-Based review - Kristi Crowe-White; J. Scott Parrott; Kim S. Stote; Melissa Gutschall; Sue Benson-Davies; Elizabeth Droke; Carol E. O'Neil; Taylor Wolfram; Paula Ziegler (Critical Reviews in Food Science and Nutrition, 2017)

Impact of 100% Fruit Juice Consumption on Diet and Weight Status of Children: An Evidence-based Review - Kristi Crowe-White; Carol E. O'Neil; J. Scott Parrott; Sue Benson-Davies; Elizabeth Droke; Melissa Gutschall; Kim s. Stote; Taylor Wolfram; Paula Ziegler (Critical Reviews in Food Science and Nutrition, 2016)

Social communities and spatiotemporal dynamics of association patterns in estuarine bottlenose dolphins - Elizabeth Murdoch Titcomb; Greg O'Corry‐Crowe; Elizabeth F. Hartel; Marilyn S. Mazzoil (Marine Mammal Science, 2015)
Network analysis has recently been used to delve into the dynamics of cetacean sociality. Few studies, however, have addressed how habitat shape influences sociality, specifically how linear water bodies constrain the space where individuals might interact. We utilized network and spatiotemporal analyses to investigate association patterns and community structure in a bottlenose dolphin population in a linear estuarine system, the Indian River Lagoon ( IRL ), Florida. Using sighting histories from a multiyear photo‐identification study we examined association patterns for 185 individuals collected over a 6.5 yr period (2002–2008). The population was highly differentiated ( S = 0.723) and organized into six distinct social communities ( Q = 0.544), spread in an overlapping pattern along the linear system. Social organization differed between communities, with some displaying highly interconnected networks and others comprising loosely affiliated individuals with more ephemeral associations. Temporal patterns indicated short‐term associations were a significant feature of the fission‐fusion dynamics of this population. Spatial analyses revealed that social structure was shaped by an individual's ranging patterns and by social processes including preference and avoidance behavior. Finally, we found that habitat “narrowness” may be a major driving force behind the sociality observed.

HIV eradication symposium: will the brain be left behind? - B. J. Brew; K. Robertson; E. J. Wright; M. Churchill; S. M. Crowe; L. A. Cysique; S. Deeks; J. V. Garcia; B. Gelman; L. R. Gray; T. Johnson; J. Joseph; et al. (Journal of NeuroVirology, 2015)

Context- and density-dependent effects of introduced oysters on biodiversity - Dannielle S. Green; Tasman P. Crowe (Biological Invasions, 2014)

Impacts of the invasive alga Sargassum muticum on ecosystem functioning and food web structure - Tânia Salvaterra; Dannielle S. Green; Tasman P. Crowe; Eoin J. O’Gorman (Biological Invasions, 2013)

Effects of Non-indigenous Oysters on Ecosystem Processes Vary with Abundance and Context - Dannielle S. Green; Carlos Rocha; Tasman P. Crowe (Ecosystems, 2013)

Regional genomic instability predisposes to complex dystrophin gene rearrangements - Junko Oshima; Daniel B. Magner; Jennifer A. Lee; Amy M. Breman; Eric S. Schmitt; Lisa D. White; Carol A. Crowe; Michelle Merrill; Parul Jayakar; Aparna Rajadhyaksha; Christine M. Eng; Daniela del Gaudio (Human Genetics, 2009)

Neurodegeneration and Ageing in the HAART Era - Bruce J. Brew; S. M. Crowe; A. Landay; Lucette A. Cysique; Gilles Guillemin (Journal of Neuroimmune Pharmacology, 2009)

Disturbance of intertidal soft sediment assemblages caused by swinging boat moorings - R. J. H. Herbert; T. P. Crowe; S. Bray; M. Sheader (Hydrobiologia, 2009)

Histamine induces interleukin-6 expression in the human synovial sarcoma cell line (SW982) through the H1 receptor - S. L. Wang; S. Malany; Q. Wang; M. A. Santos; P. D. Crowe; R. A. Maki (Inflammation Research, 2006)

The information content of Doppler ultrasound signals from the fetal heart - S. A. Shakespeare; J. A. Crowe; B. R. Hayes-Gill; K. Bhogal; D. K. James (Medical & Biological Engineering & Computing, 2001)

Application of empirical mode decomposition to heart rate variability analysis - J. C. Echeverría; J. A. Crowe; M. S. Woolfson; B. R. Hayes-Gill (Medical & Biological Engineering & Computing, 2001)

DRIED DOLPHIN BLOOD ON FISHERY OBSERVER RECORDS PROVIDES DNA FOR GENETIC ANALYSES - L. S. Eggert; C. A. Lux; G. M. O'corry‐Crowe; A. E. Dizon (Marine Mammal Science, 1998)

Phylogeography, population structure and dispersal patterns of the beluga whale Delphinapterus leucas in the western Nearctic revealed by mitochondrial DNA - G. M. O'Corry‐Crowe; R. S. Suydam; A. Rosenberg; K. J. Frost; A. E. Dizon (Molecular Ecology, 1997)
The recent evolutionary history, population structure and movement patterns of beluga whales in the western Nearctic were inferred from an analysis of mitochondrial DNA control region sequence variation of 324 whales from 32 locations representing five summer concentration areas in Alaska and north‐west Canada. Phylogenetic relationships among haplotypes were inferred from parsimonious networks, and genetic subdivision was examined using haplotypic frequency‐based indices and an analysis of variance method modified for use with interhaplotypic distance data. MtDNA relationships were characterized by a series of star‐like phylogenies which, when viewed in conjunction with information on haplotype frequency and distribution, suggested a rapid radiation of beluga whales into the western Nearctic following the Pleistocene, and an early divergence of the Beaufort Sea from the Chukchi and Bering Seas subpopulations. Overall nucleotide diversity was low (0.51%) yet all major summering concentrations were significantly differentiated (Φ ST = 0.33) from one another. Stratification of samples by gender and age from the three northernmost subpopulations suggested that female cohorts from neighbouring subpopulations were more differentiated than males. Further stratification of adult animals by age revealed that older adults were substantially less subdivided among locations than younger adults, particularly for males, suggesting that dispersal, although limited, is biased toward older adult males. Overall, the patterns of mtDNA variation in beluga whales indicated that the summering concentrations are demographically, if not phyletically distinct. Population structure appears to be maintained primarily by natal homing behaviour, while asymmetries in dispersal may be associated with the type of mating system.

Detection of fetal electrocardiogram signals using matched filters with adaptive normalisation - N. M. Gibson; M. S. Woolfson; J. A. Crowe (Medical & Biological Engineering & Computing, 1997)

Niska: A maincrop chipping potato cultivar with high specific gravity and good quality after storage - D. R. Lynch; D. Kichefski; S. Peloquin; C. S. Schaupmeyer; L. la Croix; D. Waterer; Wm. T. Andrew; J. Holley; N. Crowe; B. McConnell; G. A Nelson; B. Rex (American Journal of Potato Research, 1991)

Ribosomal RNA gene number and sequence divergence in the diploid-tetraploid species pair of north American hylid tree frogs - L. A. Toivonen; D. T. Crowe; R. J. Detrick; S. W. Klemann; J. C. Vaughn (Biochemical Genetics, 1983)